2007
DOI: 10.1097/scs.0b013e3180534421
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Autologous Cartilage, Acellular Cadaveric Dermis, Lyophilized Bovine Pericardium, and Irradiated Bovine Tendon

Abstract: The purpose of this study was to compare the volumetric and histologic changes of the acellular cadaveric dermis, lyophilized bovine pericardium, irradiated bovine tendon, and autologous cartilage transplanted subcutaneously in the rats. Four different kinds of implants were placed in subcutaneous pockets of the dorsum of 40 Wister rats. The implants with the subcutaneous pockets were retrieved in the first, fourth, eighth, and 12th weeks after implantation. The size and histologic change of each implant were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…For this purpose, the scaffolds are chemically cross-linked [3], [7], [8] or seeded with growth factors [9]. A diversity of acellular tissues is used for this purpose, such as dermis [5], [10][12], pericardium [7], [13], ligaments and tendons [6], [14] or small intestine submucosa [3], [5], [15]. These tissues mostly originate from human, bovine, caprine, equine or porcine donors [15].…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, the scaffolds are chemically cross-linked [3], [7], [8] or seeded with growth factors [9]. A diversity of acellular tissues is used for this purpose, such as dermis [5], [10][12], pericardium [7], [13], ligaments and tendons [6], [14] or small intestine submucosa [3], [5], [15]. These tissues mostly originate from human, bovine, caprine, equine or porcine donors [15].…”
Section: Introductionmentioning
confidence: 99%
“…Craft and May chose bovine collagen after Hwang et al had demonstrated the superiority of bovine collagen in nasal tip augmentation in terms of angiogenesis, invasion of host fibroblasts, and deposition of collagen fibers when compared with human cadaveric dermis. 8 In our review of the literature, the use of FBADM as a sling for the lower third of the expander pocket has not yet been reported. In addition to type I collagen, the primary collagen of human skin, FBADM is rich in type III collagen.…”
Section: Discussionmentioning
confidence: 97%
“…Acellular dermal matrix has been reported to decrease inflammatory response, infection rates, and implant rejection. 38 Unfortunately, the use of acellular dermal matrix poses a greater financial burden on patients. Banking any acellular dermal matrix excess at the time of breast reconstruction for a subsequent nipple reconstruction can alleviate such costs.…”
Section: Discussionmentioning
confidence: 99%